Cover, Editors, and Table of Content of ATBES Vol.1 No.2 Sept 2017 - Setyawati, Iriani (Advances in Tropical Biodiversity and Environmental Sciences, 2017)
Advances in Tropical Biodiversity and Environmental Sciences (ATBES) is a scientific journal published since 2017. The journal consistently publishes twice a year (Pebruary and September). The journal is registered in DOAJ. ATBES is employing a Cross Check Ref. to prevent any suspected plagiarism in the manuscripts.